Functional reconstitution of the solubilized Arabidopsis thaliana STP1 monosaccharide-H+ symporter in lipid vesicles and purification of the histidine tagged protein from transgenic Saccharomyces cerevisiae. - Stolz, Jürgen; Stadler, Ruth; Opekarová, Miroslava; Sauer, Norbert (Plant Journal, 1994)
Complete DNA sequences encoding the Arabidopsis thaliana STP1 monosaccharide/H+ symporter or a histidine-tagged STP1-His6 protein were expressed in baker's yeast Saccharomyces cerevisiae. Both wild-type STP1 and the recombinant his-tagged protein were located in the plasma membranes of transformed yeast cells. The C-terminal modification caused no loss of transport activity compared with the wild-type protein. Anti-STP1-antibodies were used to confirm the identity of the protein in yeast and to compare the apparent molecular weights of STP1 proteins in membrane extracts from yeast or Arabidopsis thaliana. Purified yeast plasma membranes were fused with proteoliposomes consisting of Escherichia coli lipids and beef heart cytochrome-c oxidase. Addition of ascorbate/TMPD/cytochrome-c to these fused vesicles caused an immediate formation of membrane potential (inside negative; monitored with [3H]tetraphenylphosphonium cations) and a simultaneous, uncoupler-sensitive influx of D-glucose into the energized vesicles. STP1-His6 protein is functionally active after solubilization with octyl-beta-D-glucoside, which was shown by insertion of the protein into proteoliposomes by detergent dilution and determination of the resulting transport capacity. Detergent extracts from either total membranes or plasma membranes of transgenic yeast cells were used for one-step purification of the STP1-His6 protein on Ni(2+)-NTA columns. The identity of the purified protein was checked by immunoblotting and N-terminal sequencing.